The CB1 cannabinoid receptor agonist reduces L-DOPA-induced motor fluctuation and ERK1/2 phosphorylation in 6-OHDA-lesioned rats - Song L; Yang X; Ma Y; Wu N; Liu Z (Dove Medical Press, 2014)
Lu Song,* Xinxin Yang,* Yaping Ma, Na Wu, Zhenguo Liu Department of Neurology, Xinhua Hospital, Shanghai Jiao Tong University School of Medicine, People’s Republic of China *These authors contributed equally to this work Abstract: The dopamine precursor L-3,4-dihydroxyphenylalanine (L-DOPA) has been used as an effective drug for treating dopamine depletion-induced Parkinson’s disease (PD). However, long-term administration of L-DOPA produces motor complications. L-DOPA has also been found to modify the two key signaling cascades, protein kinase A/dopamine- and cAMP-regulated phosphoprotein of 32 kDa (DARPP-32) and extracellular signal-regulated kinases 1 and 2 (ERK1/2), in striatal neurons, which are thought to play a pivotal role in forming motor complications. In the present study, we tested the possible effect of a CB1 cannabinoid receptor agonist on L-DOPA-stimulated abnormal behavioral and signaling responses in vivo. Intermittent L-DOPA administration for 3 weeks induced motor fluctuation in a rat model of PD induced by intrastriatal infusion of dopamine-depleting neurotoxin 6-hydroxydopamine (6-OHDA). A single injection of a CB1 cannabinoid receptor agonist WIN-55,212-2 had no effect on L-DOPA-induced motor fluctuation. However, chronic injections of WIN-55,212-2 significantly attenuated abnormal behavioral responses to L-DOPA in 6-OHDA-lesioned rats. Similarly, chronic injections of WIN-55,212-2 influence the L-DOPA-induced alteration of DARPP-32 and ERK1/2 phosphorylation status in striatal neurons. These data provide evidence for the active involvement of CB1 cannabinoid receptors in the regulation of L-DOPA action during PD therapy. Keywords: striatum, the CB1 receptor agonist WIN-55,212-2, 6-hydroxydopamine, Parkinson’s disease, motor fluctuation, L-DOPA